Use of Microdilution Panels with and without β-Lactamase Inhibitors as a Phenotypic Test for β-Lactamase Production among Escherichia coli, Klebsiella spp., Enterobacter spp., Citrobacter freundii, and Serratia marcescens - Thomson, Kenneth S. (American Society for Microbiology, 1999)
Over the past decade, a number of new β-lactamases have appeared in clinical isolates of Enterobacteriaceae that, unlike their predecessors, do not confer β-lactam resistance that is readily detected in routine antibiotic susceptibility tests. Because optimal methodologies are needed to detect these important new β-lactamases, a study was designed to evaluate the ability of a panel of various β-lactam antibiotics tested alone and in combination with β-lactamase inhibitors to discriminate between the production of extended-spectrum β-lactamases, AmpC β-lactamases, high levels of K1 β-lactamase, and other β-lactamases in 141 isolates of Escherichia coli, Klebsiella pneumoniae, Klebsiella oxytoca, Enterobacter cloacae, Enterobacter aerogenes, Citrobacter freundii, and Serratia marcescens possessing well-characterized β-lactamases. The microdilution panels studied contained aztreonam, cefpodoxime, ceftazidime, cefotaxime, and ceftriaxone, with and without 1, 2, and 4 μg of clavulanate per ml or 8 μg of sulbactam per ml and cefoxitin and cefotetan with and without 8 μg of sulbactam per ml. The results indicated that a minimum panel of five tests would provide maximum separation of extended-spectrum β-lactamase high AmpC, high K1, and other β-lactamase production in Enterobacteriaceae. These included cefpodoxime, cefpodoxime plus 4 μg of clavulanate per ml, ceftazidime, ceftriaxone, and ceftriaxone plus 8 μg of sulbactam per ml. Ceftriaxone plus 2 μg of clavulanate per ml could be substituted for cefpodoxime plus 4 μg of clavulanate per ml without altering the accuracy of the tests. This study indicated that tests with key β-lactam drugs, alone and in combination with β-lactamase inhibitors, could provide a convenient approach to the detection of a variety of β-lactamases in members of the family Enterobacteriaceae.